Application of ultrasound techniques in Solid-Liquid fluidized bed. (15th May 2022) - Hossein, Fria; Materazzi, Massimiliano; Errigo, Matteo; Angeli, Panagiota; Lettieri, Paola
Highlights: This paper describes an application of ultrasound techniques to solid–liquid fluidized beds. The ultrasonic methods are used for obtaining velocity profiles, particle size distribution, and solids volume fraction. The solid velocity profiles and particle size distributions were measured for four different sizes of glass particles ranging from 500 μm to 1250 μm at a solid volume fraction of 35%. The importance of the techniques as a diagnostic tool to investigate the particles segregation behaviour in solid–liquid fluidized beds at different fluidization conditions are reported. Abstract: This paper describes an application of ultrasound techniques to solid–liquid fluidized beds. The ultrasonic methods, experimental setups, and the signal processing for obtaining velocity profiles, particle size distribution, and solids volume fraction are discussed. The techniques are based on the measurement of the ultrasound attenuation coefficient, sound speed, and frequency shift of the propagated sound wave. The ultrasound propagation speed in solid–liquid fluidized bed was measured to be between 1504 m/s and 1565 m/s for glass particles with volume fractions spanning from 27% to 70% in water. The solid velocity profiles were measured for liquid superficial velocities varying from 0.84 cm/s to 4.24 cm/s. The particle size distributions were measured for four different sizes of glass particles ranging from 500 μm to 1250 μm at a solid volume fraction of 35%. This paper also reports the importance of the techniques as a diagnostic tool to investigate the particles segregation behaviour in solid–liquid fluidized beds at different fluidization conditions. The results indicated that ultrasound techniques are a powerful tool that can characterise in real-time highly concentrated solid–liquid systems.